Performance of honey bee colonies under a long‐lasting dietary exposure to sublethal concentrations of the neonicotinoid insecticide thiacloprid - Siede, Reinhold (John Wiley & Sons, Ltd, 2017)

(untitled) (Pest Manag Sci)
BACKGROUND: Substantial honey bee colony losses have occurred periodically in the last decades. The drivers for these losses are not fully understood. The influence of pests and pathogens are beyond dispute, but in addition, chronic exposure to sublethal concentrations of pesticides has been suggested to affect the performance of honey bee colonies. This study aims to elucidate the potential effects of a chronic exposure to sublethal concentrations (one realistic worst‐case concentration) of the neonicotinoid thiacloprid to honey bee colonies in a three year replicated colony feeding study. RESULTS: Thiacloprid did not significantly affect the colony strength. No differences between treatment and control were observed for the mortality of bees, the infestation with the parasitic mite Varroa destructor and the infection levels of viruses. No colony losses occurred during the overwintering seasons. Furthermore, thiacloprid did not influence the constitutive expression of the immunity‐related hymenoptaecin gene. However, upregulation of hymenoptaecin expression as a response to bacterial challenge was less pronounced in exposed bees than in control bees. CONCLUSION: Under field conditions, bee colonies are not adversely affected by a long‐lasting exposure to sublethal concentrations of thiacloprid. No indications were found that field‐realistic and higher doses exerted a biologically significant effect on colony performance. © 2017 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.